Singing well-becoming: Student musical therapy case studies - Murphey, Tim (Studies in Second Language Learning and Teaching, 2014)
Much research supports the everyday therapeutic and deeper socialneurophysiological influence of singing songs alone and in groups (Austin, 2008; Cozolino, 2013; Sacks, 2007). This study looks at what happens when Japanese students teach short English affirmation songlet-routines to others out of the classroom (clandestine folk music therapy). I investigate 155 student-conducted musical case studies from 7 semester-long classes (18 to 29 students per class) over a 4-year period. The assignments, their in-class training, and their results are introduced, with examples directly from their case studies. Each class published their own booklet of case studies (a class publication, available to readers online for research replication and modeling). Results show that most primary participants enjoyed spreading these positive songlets as they became “well-becoming agents of change” in their own social networks. “Well-becoming” emphasizes an agentive action or activity that creates better well-being in others, an action such as the sharing or teaching of a songlet. The qualitative data reveals a number of types of well-becoming such as social and familial bonding, meaning-making, teaching-rushes, and experiencing embodied cognition. The project also stimulated wider network dissemination of these well-becoming possibilities and pedagogical insights.